PERAN BPJS KESEHATAN KABUPATEN BUNGO DALAM MENINGKATKAN KEPESERTAAN MASYARAKAT - Mela Sari; Meri Marliza (Jurnal Administrasi Sosial dan Humaniora, 2023)
Health insurance was a guarantee in the form of health protection in order to obtain health care benefits and protection in meeting basic health needs provided to everyone who has paid contributions or whose contributions have been paid by the government. To fulfill this health insurance needed the role of BPJS to increased community participation to become members of BPJS.This research used a descriptive method with a qualitative approach by using purposive sampling method with total sample were 7 informants consisted of the Bungo branch of BPJS and society. The data analysis technique used an alternative model by Miles Huberman.The results of the study showed that in increasing membership, the BPJS in Bungo regency carried out the role by 3 activity programs, namely Direct Information Providing (PIL), Market Penetration for Participant Recruitment, and BPJS Health Promotion.